2020
DOI: 10.1186/s12913-020-05879-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing hospital performance indicators. What dimensions? Evidence from an umbrella review

Abstract: Background Patients’ increasing needs and expectations require an overall assessment of hospital performance. Several international agencies have defined performance indicators sets but there exists no unanimous classification. The Impact HTA Horizon2020 Project wants to address this aspect, developing a toolkit of key indicators to measure hospital performance. The aim of this review is to identify and classify the dimensions of hospital performance indicators in order to develop a common language and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 20 publications
0
27
0
2
Order By: Relevance
“…The resulting dimensions from this project were clinical effectiveness, efficiency, HCW orientation, responsive governance, safety, and patient-centeredness. However, studies have shown that there are still some gaps in this model and issues concerning the dimensions investigated [ 13 , 14 ]. Additionally, the Organization for Economic Co-operation and Development (OECD) launched the Health Care Quality Indicator (HCQI) project in 2006; it aimed to develop key performance indicators (KPIs) to compare quality in health care at the international level and achieve international benchmarking.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting dimensions from this project were clinical effectiveness, efficiency, HCW orientation, responsive governance, safety, and patient-centeredness. However, studies have shown that there are still some gaps in this model and issues concerning the dimensions investigated [ 13 , 14 ]. Additionally, the Organization for Economic Co-operation and Development (OECD) launched the Health Care Quality Indicator (HCQI) project in 2006; it aimed to develop key performance indicators (KPIs) to compare quality in health care at the international level and achieve international benchmarking.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting dimensions from this project were clinical effectiveness, efficiency, HCW orientation, responsive governance, safety, and patientcenteredness. However, studies have shown that there are still some gaps in this model and issues concerning the dimensions investigated [13,14]. Additionally, the Organization for Economic Co-operation and Development (OECD) launched the Health Care Quality Indicator (HCQI) project in 2006; it aimed to develop key performance indicators (KPIs) to compare quality in health care at the international level and achieve international benchmarking.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we assessed only one quality outcome, mortality. Hospital quality is a complex and multi-faceted construct [ 21 ] which cannot be summarized by hospital mortality alone, or by any single metric. However, mortality is a key performance indicator, and the methods of HS-TM and regression can be applied to other outcomes such that the findings of improved interpretability and credibility are not necessarily specific to mortality only.…”
Section: Discussionmentioning
confidence: 99%